Pelatihan Penggunaan Modul Pemahaman Diri Siswa Berbasis Karakter Bagi Guru-Guru SD Gugus III Kec. Gunungsari - A. Hari Witono; Heri Hadi Saputra; Prayogi Dwina Angga; Heri Setiawan; M. Okta D. S. F. M. Marijo (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2022)
The facts in the field show that not many elementary school teachers have upgraded their skills through various trainings, one of which is the competence to conduct guidance and counseling. Various alternative solutions can be used as problem solving, namely training on the use of character-based student self-understanding modules to help class teachers and students in implementing counseling guidance in elementary schools. The method used is lecture, question and answer or discussion and mentoring. The target audience is elementary school teachers who are members of cluster 3, Kec. Gunungsari. The place of implementation is at SDN 1 Kekeri. The participants were 10 teachers and 5 principals. The implementation of this service activity is divided into four stages of activity, namely opening and greetings, material presentation, questions and answers, and the practice of using the module by the teacher. In general, the activities went quite smoothly. There was an increase in the teacher's understanding of the use of the module. The post-activity follow-up for each participant is implementing the module to students. The service team will provide field assistance to ensure participants are able to carry out according to the designations and instructions in the module.